Sustainable development discourse on the environmental crisis in an unequal world A Socio-critical reading - Ben Kraiem, Aida Elhadi (Journal of Humanities & Social Sciences, 2025)
This paper presents some keys that will facilitate the reader, both informed and uninformed, to build a comprehensive vision of the most significant aspects of the sustainable development discourse. Our goal is to contribute to the debate on the relationship between sustainable development and the environmental crisis in a changing world whose social and economic ties and systems are characterized by expansion, overlap and intertwining. To clarify the nature of this relationship, we have begun with an introduction in which we have placed that relationship in its global context; to highlight the horizontal expansion of the capitalist mode of production, i.e. the extent to which human intervention in nature has reached and the effects of that intervention on all aspects of social, economic and political life; and also in its cultural and social context, where environmental awareness has increased since the early seventies and the pace of demands to put an end to globalization and the escalating environmental problems it produces has increased. Then, relying on critical sociology and discourse analysis, we present and discuss what the United Nations, as an international organization that brings together a group of countries within a single political framework, proposes in terms of policies and orientations related to economic growth and the environmental crisis. The paper revealed that the assumptions of the sustainable development discourse, which is advocated by the United Nations and its subsidiary bodies in the field of development, and the policy packages they propose, ignore the depth of the gap between the North and the South of the planet. As a result, it seems that the countries of the South must reconsider the existing models presented by international organizations concerned with sustainable development and introduce modifications that are compatible with their social, political and cultural contexts.